Signalfunktion and Kodierungsgrad von sprachlichen Merkmalen in Gerichtsurteilen - Engberg, Jan (HERMES - Journal of Language and Communication in Business, 1992)
This article investigates the relations between the textual conventions of a text genre and the speech acts performed within this genre. The starting point of the study is a critical view upon Katharina Reiss’ concept of "Textsortenkonventionen". It is stated that a mainly quantitative concept as Reiss’ cannot adequatly guide the translator in his search for the appropriate translation equivalent, and that a qualitative concept of textual convention has to be developed to fill this gap. As an example, an analysis of the speech act [report] within the text genre "legal judgements in Civil Law cases" is presented. As a result of the analysis, some of the conventions of the text genre are said to be coded signals for the speech acts performed within the genre. On the basis of these results an attempt is made to develop a theoretical concept that may describe the relation between degree of conventionalisation and the signal quality of linguistic elements within texts.